2023
DOI: 10.20998/2220-4784.2022.02.10
|View full text |Cite
|
Sign up to set email alerts
|

Bottomhole Formation Zone Restoration Mechanisms and Methods

Abstract: The importance of the choice of well exploitation methods is analyzed. Mechanical methods applicable in carbonate reservoirs are discussed. To maintain the efficiency of field development, it is important to maintain the productivity of wells at the planned level throughout the entire production period by increasing their productivity. Productivity increase, skin effect reduction is achieved with the help of acid treatment, the main principle of which is rock dissolution to form a man-made network of microchan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…The basic principles of restoring the productivity of wells plugged during their drilling and operation using acid treatments were studied in [10]. It is shown that many wells that, as a result of drilling, well workover after long-term operation, do not produce production due to complete or partial clogging.…”
mentioning
confidence: 99%
“…The basic principles of restoring the productivity of wells plugged during their drilling and operation using acid treatments were studied in [10]. It is shown that many wells that, as a result of drilling, well workover after long-term operation, do not produce production due to complete or partial clogging.…”
mentioning
confidence: 99%